Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph182413343
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Factors in Advanced Platelet-Rich Fibrin (A-PRF) Reduce Postoperative Complications after Mandibular Third Molar Odontectomy

Abstract: Surgical removal of impacted mandibular third molars constitutes one of the most frequently performed procedures within oral surgery. This surgery procedure is associated with many post-operative complications. Advanced platelet-rich fibrin (A-PRF) belongs to the second generation of platelet concentrates and is rich in numerous growth factors. The aim of this study was to assess the influence of A-PRF on selected clinical features following the surgical removal of impacted mandibular third molars. The researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…This study showed that pain significantly decreased in both HA and A-PRF groups compared to the control group. These results agreed with several previous studies demonstrating the effectiveness of HA gel or A-PRF in reducing postoperative pain [ 1 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study showed that pain significantly decreased in both HA and A-PRF groups compared to the control group. These results agreed with several previous studies demonstrating the effectiveness of HA gel or A-PRF in reducing postoperative pain [ 1 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…The antiedematous properties of HA could be attributed to its osmotic buffering capabilities in addition to delaying leukocyte migration via adhering to its receptor CD44 [ 29 , 30 ], and the antiedematous properties of A-PRF could be attributed to its ability in minimizing the risk of inflammation in the surgical site [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors that determine the difficulty of the surgical procedure of avulsion of the third molar are depth and space available for removal of the impacted mandibular third molar, the angulation of the tooth, root spacing, size of the bone septum, presence or absence of a dilated tooth follicle, periodontal space, bone density, and the relation to the inferior alveolar nerve. Other factors that influence the occurrence of non-infectious complications after this procedure are the experience of the surgeon, the choice of the operating method, the time of the procedure, and soft tissue trauma (14). The regenerative potential of platelets has been harnessed and used in the field of oral and maxillofacial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessed various modalities including systemic or local corticosteroids 3 , 18 , 19 , natural substance 2 , platelet concentrates 20 , 21 , and adjuvant laser therapy 22 for reducing postoperative swelling and trismus or pain after surgical extraction of M3M. For several decades in the area of dentistry or maxillofacial surgery, HUD, has been investigated in only a few studies regarding postoperative swelling after guided bone regeneration (GBR) with simultaneous dental implant placement 23 or efficacy of anesthesia for irreversible pulpitis 9 .…”
Section: Discussionmentioning
confidence: 99%